Food Safety Problems in the World and in Turkey: Solutions Offered from the Perspective of Social Responsibility - Topal, R. Seminur (EMERALD GROUP PUBLISHING LTD, 2005)
At the beginning of the new millennium, looking through national / international perspectives and analysing different projections and conclusions, investigation of future, interrogation of systems and ourselves will be useful. It is necessary to talk about the past and the future in a global perspective when the world population is more than 6 billion and expected to increase around another 2 billion in the next 25 years. Natural resources are limited instead of increased population in the world around. However the growth of technology and communication level, there are so many hazard factors in the life for many developing countries. Simply maintaining current levels of food availability will require rapid production increases without destroying natural resources. Having a good nutritional status for all human societies, everybody must have to think us as instead of myself. The world has expanded beyond the global village to include the global market where there is ever-increasing mobility of capital, labour and goods, in the recent years. Globalisation is not only a question of size, but also of kind: it is inextricably linked to privatisation. It stimulated major economic restructuring in both developed and developing countries, and has greatly changed the balance of public and private sectors. Mostly agricultural production for export is seen as one of the driving forces of development. Harmonisation through the setting of international regulations and standards still needs considerable efforts. So that potential benefits and defects, the outcomes of globalisations are mixed and also demographic and production relationship correlations are changed dramatically. In the world natural food and water sources have been reduced, when population increased speedily and environments pollution has become dramatic. In spite of urbanisation the majorities are in rural areas. The information revolutions and scientific / technological challenges also created a major difference between developed and developing countries. Genetically modified organisms and foods are the most important question at this time in the world. Again the differences about sharing chance of the sources between rich and poor countries are another important inequity. Food insecurity means that lacking access to sufficient amounts of safe and nutritious food and are therefore not consuming enough for an active and healthy life. There are so many reasons for the unavailability of food, inadequate purchasing power or inappropriate utilisation at household level. The linkages between demographic motivations, poverty and environmental degradation, their relationships and implications according to the development programs and planning will try to be discussed in this article. Nutritional and energy requirements, some nutritional deficiencies, reflections on the commercial life, food security programs, and better information systems on Food Insecurity and Vulnerability (FIVIMS), National Nutrition Country Profiles (NFC), farseeing of UN's, Codex Alimentarius Commission (CAC) and World Trade Organisation (WTO) will be summarised. Also it is planned to make small statistical tour on the national and international past, status, and near future on problems and expected reflections, some of the solution offers are improving strategies and increasing consciousness to consumers, developments of health -agriculture -education politics will be summarised. Governmental responsibilities and financial supports will try to be discussed. Finding food, improving life, preparing a better world must be a primer responsibility for all countries, governments, sectors and for everybody in this millennium.
Keywords: Business & Economics